2007
DOI: 10.1074/jbc.m607610200
|View full text |Cite|
|
Sign up to set email alerts
|

Carbon Monoxide Protects against Hyperoxia-induced Endothelial Cell Apoptosis by Inhibiting Reactive Oxygen Species Formation

Abstract: Hyperoxia causes cell injury and death associated with reactive oxygen species formation and inflammatory responses. Recent studies show that hyperoxia-induced cell death involves apoptosis, necrosis, or mixed phenotypes depending on cell type, although the underlying mechanisms remain unclear. Using murine lung endothelial cells, we found that hyperoxia caused cell death by apoptosis involving both extrinsic (Fasdependent) and intrinsic (mitochondria-dependent) pathways. Hyperoxia-dependent activation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
146
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(149 citation statements)
references
References 50 publications
(66 reference statements)
3
146
0
Order By: Relevance
“…We have previously shown that DISC formation during hypoxia-reoxygenation-induced endothelial cell apoptosis was inhibited by expression of the endogenous caspase-8 inhibitor FLIP (42) and of Bcl-X L (20). We also reported that DISC formation during hyperoxia-induced endothelial cell apoptosis depended on reactive oxygen species generation, and could be inhibited by carbon monoxide, as well as by inhibitors of ERK1/2 MAPK or NADPH oxidase-dependent pathways (49).…”
Section: Discussionmentioning
confidence: 91%
“…We have previously shown that DISC formation during hypoxia-reoxygenation-induced endothelial cell apoptosis was inhibited by expression of the endogenous caspase-8 inhibitor FLIP (42) and of Bcl-X L (20). We also reported that DISC formation during hyperoxia-induced endothelial cell apoptosis depended on reactive oxygen species generation, and could be inhibited by carbon monoxide, as well as by inhibitors of ERK1/2 MAPK or NADPH oxidase-dependent pathways (49).…”
Section: Discussionmentioning
confidence: 91%
“…The cytoprotective properties of HO-1 have traditionally been attributed to the by-products of heme degradation, namely bilirubin and carbon monoxide (CO). Indeed, within a narrow therapeutic range, these catalytic by-products exert powerful antioxidant [15,31], antiinflammatory [32] and anti-apoptotic effects [33][34][35], leading to reduced infarct size [16,17,[36][37]. However, emerging evidence, suggests that HO-1 may also exert cytoprotective effects, independent of heme breakdown [38] by interacting with survival signaling pathways such as PI3K-Akt and p38.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, Ilizarov and colleagues (54) observed in a mouse lung epithelial cell line that SOD2, but not SOD1 or catalase prevented hyperoxia-induced cell death. By contrast, other investigators have observed that strategies that prevent the assembly of the NAD(P)H oxidase on the plasma membrane of endothelial cells prevent hyperoxiainduced oxidant generation and cell death (55)(56)(57). Several possibilities might explain these results.…”
Section: Discussionmentioning
confidence: 89%